DEVELOPMENT OF LOGICAL THINKING IN MATHEMATICS LESSONS AMONG JUNIOR SCHOOLCHILDREN - Lola Uktamovna Urinboyeva (European Science Publishing, 2024)
The article reveals the role of mathematics in the formation and development of a child as an individual, as well as its significance in practical life. The main task of teaching mathematics in primary school, methodological principles of teaching, the content of the primary mathematics course within the National Curriculum, as well as an analysis of the features of modern teaching are presented.
Keywords: school mathematics education, content of mathematics education, mathematical activities.